The Four Winds - Hannah, Kristin (New York : St. Martin's Press, 2021)
"From Kristin Hannah, the #1 New York Times bestselling author of The Nightingale and The Great Alone, comes an epic novel of love and heroism and hope, set against the backdrop of one of America's most defining eras-the Great Depression. Texas, 1934. Millions are out of work and a drought has broken the Great Plains. Farmers are fighting to keep their land and their livelihoods as the crops are failing, the water is drying up, and dust threatens to bury them all. One of the darkest periods of the Great Depression, the Dust Bowl era, has arrived with a vengeance. In this uncertain and dangerous time, Elsa Martinelli-like so many of her neighbors-must make an agonizing choice: fight for the land she loves or go west, to California, in search of a better life. The Four Winds is an indelible portrait of America and the American Dream, as seen through the eyes of one indomitable woman whose courage and sacrifice will come to define a generation"--
Keywords: Women farmers -- Fiction; Historical fiction; Women -- Fiction; Texas -- Fiction; Historical fiction; Novels